New approach for biodegradation of Malathion pesticide by Bacillus sp. isolated from agricultural field: Bioreactor and kinetics - Geed S.R.; Sawarkar A.N.; Singh R.S.; Rai B.N. (My University, 2025)
This study is focuses on understanding bioremediation strategies for biodegrdadation of Malathion by isolating potential microbes, enhancing rate in batch packed bed bioreactor, confirming metabolites, and then proteomics. The bacterial species were isolated and identified from agricultural fields. Biodegradation of Malathion was studied by isolated species, and it was observed that Bacillus sp. S4 is more effective than Bacillus sp. S1 and Bacillus sp. S2 for Malathion bioremediation. The maximum removal efficiency of Malathion (72%) was achieved at 200 mg/L in a free cell and it was further improved to 84% in batch packed bed bioreactor at optimum pH (7.5) and temperature (32 °C). The leachate was analyzed, and two metabolites, namely, Malathion monocarboxylic acid and Succinic acid, were identified. In Monod growth kinetics, the maximum specific growth rate (0.254 per day), rate constant (119.5 mg/day) and in Andrew-Haldane inhibition kinetics, the maximum specific growth rate (0.228/day), rate constant (114.8 mg/L), and inhibition constant (348.43 mg/L) were evaluated. Identified proteins were characterized by sequential, functional, and structural analysis. The best quality hypothetical protein (NP_390682.1) from treated Malathion was used for docking calculation. The residues of major active binding sites ILE151, GLY152, ASN155, SER156, SER157, VAL159, HIS160, PRO161, GLU192, GLU195, VAL196, and ARG199 involved in interaction with binding energy 4.318 kcal/mol and dissociation constant 683697536.0 PM, were investigated. The results obtained are expected to be helpful in the practical application of Bacillus sp. S4 for the removal of Malathion from the contaminated environment under in situ conditions. © 2022 Elsevier Ltd.